Pola Komunikasi Dakwah Wahdah Islamiyah di Kabupaten Sinjai, Sulawesi Selatan - Suriati Suriati (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
The development of information technology has influenced patterns of social interaction. This should be responded by the da'wah institutions in carrying out their proselytizing (da'wah) activities. The practice of da'wah has so far been running but it is often less optimal in applying communication patterns due to unclear control groups and the difficulties in evaluating movements. As a religious organization, Wahdah Islamiyah organization in Sinjai, South Sulawesi is very active in doing proselytizing activities to the people. This study aimed at uncovering the communication patterns adopted by Wahdah Islamiyah in delivering its da'wah messages in Sinjai and how it is developed and accepted by people living in remote villages. This is a qualitative research, using the methods of da’wah communication and sociological approaches. Data were collected by conducting observation, interview, and documentation and analyzed through the process of of data reduction, data display and drawing conclusions. The results of the study found that the communication patterns applied by Wahdah Islamiyah in Sinjai consists of control groups communication in which the organization controls the Muslim preachers (da’i) and da’wah materials; tarbiyah communication by using a tiered curriculum system in learning; cadre pattern through guidance to cadres; and network communication, namely recruiting new members